Determinan Penyalahgunaan Narkoba pada Remaja di SMAN 24 Jakarta - Oki Fitriani; Sarah Handayani; Nur Asiah (ARKESMAS [Arsip Kesehatan Masyarakat], 2017)
Determinants of Drug Abuse Among Adolescents in 24 Senior High School Jakarta Introduction. The number of drug abuse in adolescents has increased dramatically. Survey conducted in2006 and 2009 shows pattern that drug abuse risk in big city is higher rather than in small city. It is alsoidentified that the risk level of drug abuse in adolescents is different from one to another. The differencesare caused by several factors. This study aims to determine some factors believed to have associationwith the risk of drug abuse in adolescents in 24 Senior High School, Jakarta.Methods. This study is a quantitative analytical research using cross sectional design. Location of thestudy was in 24 Senior High School, Jakarta. Research was conducted during March – August 2016.Population of this study was all student grade 10 and 11 in 24 Senior High School, Jakarta which is 350students. Variable dependent in this study is drug abuse risk and independent variables are individual,drug and environment characteristic. Sampling was chosen using proportional stratified randomsampling. The total sample was 91 people. Data analysis was using uni variate and bivariate analysis.Resulst. The results showed from 8 variables, only 6 variables that have relationship with the risk of drugabuse in teenagers / students. Those variables are drug factors; availability (p value = 0.000 PR = 2,595% CI 1566-3909), and the ease of getting drugs (p value = 0,009 PR = 1,7 95% CI 1114-2437),individual factors; gender (p value = 0,000 PR = 2,6 95% CI 0626-4218), and knowledge (p value =0048 PR = 1,5 95% CI 0966-2340), environmental factors; family (p value = 0.003 PR = 1,8 95% CI1174-2739), and friends (association) (p value = 0,000 PR = 2,4 95% CI 1512-3647).Conclusions. Variables that have relationship with the risk of drug abuse are drug factors (availability,the ease of getting drugs) individual factors (gender, knowladge) and environment factors (family, friend)